Asynchronous programming easier asynchronous programming with the new Visual Studio Async CTP. IN Features. - Lippert, Eric (MSDN magazine)
The next version of C# and Visual Basic will include a form of asynchronous control flow that avoids both the dangers of multithreading and the pain of writing callback methods.